Cancer-Associated Fibroblasts as a Common Orchestrator of Therapy Resistance in Lung and Pancreatic Cancer - Domen, Andreas (Cancers (Basel), 2021)
SIMPLE SUMMARY: The tumor microenvironment (TME) is increasingly believed to be involved in therapy resistance and disease progression of different cancer types. Cancer-associated fibroblasts (CAFs) are prominent components and a central player in creating this TME. In particular, lung and pancreatic cancer, two solid tumor types associated with therapy resistance and poor long-term prognosis have clear evidence of CAFs. In order to provide a more holistic approach of therapy resistance, we highlight different mechanisms of CAF contribution to tumor progression and provide a comprehensive review on how CAFs affect their response to clinical therapy and prognosis, and present an overview of novel therapies and future perspectives involving CAF-targeting agents for both cancer types. ABSTRACT: Cancer arises from mutations accruing within cancer cells, but the tumor microenvironment (TME) is believed to be a major, often neglected, factor involved in therapy resistance and disease progression. Cancer-associated fibroblasts (CAFs) are prominent and key components of the TME in most types of solid tumors. Extensive research over the past decade revealed their ability to modulate cancer metastasis, angiogenesis, tumor mechanics, immunosuppression, and drug access through synthesis and remodeling of the extracellular matrix and production of growth factors. Thus, they are considered to impede the response to current clinical cancer therapies. Therefore, targeting CAFs to counteract these protumorigenic effects, and overcome the resistance to current therapeutic options, is an appealing and emerging strategy. In this review, we discuss how CAFs affect prognosis and response to clinical therapy and provide an overview of novel therapies involving CAF-targeting agents in lung and pancreatic cancer.